Fallo 063 – 2018: la muerte de Luis Ángel Ramos Claros, interpretada desde el tipo penal de feminicidio en Garzón Huila. - Muñoz Lozada, María Alejandra; Muñoz Lozada, Fabiana (Universidad Antonio Nariño, 2021)
With the present investigative article, the intention is to analyze the ruling issued by the Second Penal Court Of The Garzon Circuit, by which it condemns Mr. Davinson Stiven Erazo Sánchez for the crime of femicide, after having caused the death of Luis Ángel Ramos Claros who towards part of the LGTBI+ community. Due to the above, the scope of Law 1761 of 2015 "Rosa Elvira Cely" regarding Feminicide vis-à-vis the Transgender community will be addressed, each time the behavior framework against gender identity in the providence object of analysis, genders an impact of importance in our society and in the rights that the LGTBI+ community seeks in Colombia, for this reason, we will delve into ¿why the crime of homicide of a person who was legally male, but whose identity is always Rooted in the female gender?